(untitled) (Journal of Bangladesh Academy of Sciences, 2012)
Ni-Zn perminvar ferrites having the compositions Co0.02Zn0.20Ni0.58Fe2.2O4 and Co0.02Zn0.28 Ni0.50Fe2.2O4 were prepared through the solid state reaction using conventional ceramic method. The homogeneous phase of perminvar ferrites has been observed from the study of X-ray diffraction. Lattice parameter of the samples was found to be 8.369, 8.372 and 8.375Å for the sample Co0.02Zn0.20Ni0.58Fe2.2O4 and 8.382, 8.383 and 8.384Å for the sample Co0.02Zn0.28 Ni0.50Fe2.2O4 sintered at 1200, 1300 and 1350°C respectively. Both the bulk density and porosity decreases with Zn content and sintering temperatures. The values of Curie temperature of the two compositions were found to be 511, 508 and 508°C (for TS = 1200, 1300 and 1350°C) for the sample of Co0.02Zn0.20Ni0.58Fe2.2O4 and 460 and 455°C (for Ts = 1300 and 1350°C) for the sample of Co0.02Zn0.28Ni0.50Fe2.2O4, respectively. Frequency dependence permeability spectra, revealed that permeability of all the samples is almost independent of frequency up to 1 MHz. It is observed that permeability increases with Zn content and hence the relative quality factor decreases with increasing Zn content. Key words: Perminvar ferrite; Curie temperature; Initial permeability; Quality factor DOI: http://dx.doi.org/10.3329/jbas.v35i2.9421 JBAS 2011; 35(2): 171-178